Economic Identity of the Acehnese People - Mansur, Mahlel (Wasatha: Jurnal Studi Islam dan Humaniora, 2023)
This research explores the unique economic identity of Aceh Province, Indonesia. With a focus on historical, cultural, and social factors that influence the economy, this research uses a qualitative approach and literature review to explore the diversity of economic sectors. Aceh's long history as a spice trading center and its position in the implementation of Islamic law after special autonomy have formed a unique economic framework. Traditional agriculture, a prosperous fishing industry, as well as tourism potential that has not yet been fully explored, are all important elements of Aceh's economic identity. However, challenges such as vulnerability to natural disasters, the influence of armed conflict, and restrictions in the implementation of Islamic law, have influenced the economic dynamics of this region. This research concludes that by exploiting the potential of the large tourism sector, technological innovation, and collaboration between stakeholders, the people of Aceh have the opportunity to strengthen their economy while facing existing challenges. This provides the basis for ongoing policy development to support inclusive and sustainable economic growth in Aceh.